Symplectic Computation of Hamiltonian Systems (I) (Journal of Computational Mathematics, 2002)
We get $τ^6$-terms of the formal energy of the mid-point rule, and use the mathematical pendulum to test the convergence of the formal energy.
Keywords: Mid-point rule; Formal energy.